ULK1 Inhibition as a Targeted Therapeutic Strategy for Psoriasis by Regulating Keratinocytes and Their Crosstalk With Neutrophils - Qiu, Xiaonan; Zheng, Lin; Liu, Xiuting; Hong, Dan; He, Mintong; Tang, Zengqi; Tian, Cuicui; Tan, Guozhen; Hwang, Sam; Shi, Zhenrui; Wang, Liangchun (Frontiers in Immunology, 2021)
Psoriasis is a common inflammatory skin disease resulting from an interplay of keratinocytes and immune cells. Previous studies have identified an essential role of autophagy in the maintenance of epidermal homeostasis including proliferation and differentiation. However, much less is known about the role of autophagy-related proteins in the cutaneous immune response. Herein, we showed that ULK1, the key autophagic initiator, and its phosphorylation at Ser556 were distinctively decreased in the epidermis from lesional skin of psoriasis patients. Topical application of SBI0206965, a selective ULK1 inhibitor, significantly attenuated epidermal hyperplasia, infiltration of neutrophils, and transcripts of the psoriasis-related markers in imiquimod (IMQ)-induced psoriasiform dermatitis (PsD). In vitro, ULK1 impairment by siRNA and SBI0206965 arrested cell proliferation and promoted apoptosis of keratinocytes, but had a marginal effect on the expression of proinflammatory mediators under steady status. Surprisingly, SBI0206965 blocked the production of chemokines and cytokines in keratinocytes stimulated by neutrophils. Of interest, the pro-apoptotic and anti-inflammatory effects of ULK1 inhibition cannot be fully replicated by autophagic inhibitors. Our findings suggest a self-regulatory process by downregulating ULK1 to maintain the immune homeostasis of psoriatic skin via regulating keratinocytes and their crosstalk with neutrophils, possibly through both autophagy-dependent and independent mechanisms. ULK1 might be a potential target for preventing or treating psoriasis.